Patient use of online medical records: an application of technology acceptance framework. (22nd October 2019) - Mukhopadhyay, Surma; Basak, Ramsankar; Carpenter, Darrell; Reithel, Brian J.
Abstract : Purpose: Little is known about factors that affect patient use of online medical records (OMR). Specifically, with rising vulnerability concerns associated with security and privacy breaches, patient use of OMR requires further attention. This paper aims to investigate patient use of OMR. Using the Unified Theory of Acceptance and Use of Technology (UTAUT), factors affecting continued use of OMR were examined. Design/methodology/approach: The Health Information National Trends Survey 5 (HINTS 5), Cycle 1 data were used. This is an ongoing nation-wide survey sponsored by the National Cancer Institute (NCI) of the USA. The subjects were 31-74 years old with access to the Internet. Descriptive information was projected to the US population. Findings: In total, 765 respondents representing 48.7 million members of the US population were analyzed. Weighted regression results showed significant effects of perceived usefulness, visit frequency and provider encouragement on continued use of OMR while vulnerability perception was not significant. Moderating effects of these variables were also noted. Perceived usefulness and provider encouragement emerged as important predictors. Practical implications: Insights may help design interventions by health-care providers and policymakers. Social implications: Insights should help patient empowerment and developers with designing systems. Originality/value: This is the first study to examine health-care consumers' continued use of OMR using nationally representative data and real-world patients, many of who have one or more chronic diseases (e.g. diabetes, hypertension, asthma) or are cancer survivors. Results highlight factors helping or hindering continuing OMR use. As such, insights should help identify opportunities to increase the extent of use, project future OMR usage patterns and spread the benefits of OMR, including bringing forth positive health outcomes.